Monoterpene indole alkaloid azine derivatives as MDR reversal agents. Issue 2 (15th January 2018) - Paterna, Angela; Khonkarn, Ruttiros; Mulhovo, Silva; Moreno, Alexis; Madeira Girio, Patricia; Baubichon-Cortay, Hélène; Falson, Pierre; Ferreira, Maria-José U.
Graphical abstract: Highlights: Twenty-four indole alkaloid derivatives were evaluated as MDR reversers. Compounds bearing an aromatic azine moiety showed the best anti-MDR activity. Selective inhibition of MRP1- or P-gp-mediated efflux was observed. Some compounds were able to selectively kill MRP1-overexpressing cells. Some compounds induced apoptosis by increasing glutathione depletion. Abstract: Aiming at generating a library of bioactive indole alkaloid derivatives as multidrug resistance (MDR) reversers, two epimeric indole alkaloids (1 and 2 ) were submitted to chemical transformations, giving rise to twenty-four derivatives (5 -28 ), bearing new aromatic or aliphatic azine moieties. The structure of the compounds was established by 1D and 2D NMR (COSY, HMBC, HMQC and NOESY) experiments. Two different strategies were employed for assessing their anti-MDR potential, namely through the evaluation of their activity as inhibitors of typical MDR ABC transporters overexpressed by cell transfection, such as ABCB1 (P-gp), ABCC1 (MRP1), and ABCG2 (BCRP), or by evaluating their ability as collateral sensitivity (CS) agents in cells overexpressing MRP1. A considerable MDR reversing activity was observed for compounds bearing the aromatic azine moiety. The strongest and most selective P-gp inhibition was found for the epimeric azines 5 and 6, bearing a para -methylbenzylidene moiety. Instead, compounds 17 and 18 that possess a di-substituted benzylidene portion with methoxy and hydroxyl groups, selectively inhibited MRP1 drug-efflux. None of these compounds inhibited BCRP. Compounds 5, 6 and 18 were further investigated in drug combination experiments, which corroborated their anti-MDR potential. Moreover, it was observed that compound 12, with an aromatic azine moiety, and compounds 23 -26, sharing a new aliphatic substituent, displayed a CS activity, selectively killing MRP1-overexpressing cells. Among these last compounds, it could be established that addition of 19, 23 and 25 to MRP1-overexpressing cells led to glutathione depletion triggering cell death through apoptosis.